2003
DOI: 10.1046/j.1365-2257.2003.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

α-Thalassemia 2, 3.7 kb deletion and hemoglobin AC heterozygosity in pregnancy: a molecular and hematological analysis

Abstract: alpha-Thalassemia is a synthesis hemoglobinopathy with a worldwide distribution. alpha-thalassemia-23.7kb (alpha-Thal23.7kb) was investigated by PCR and standard hematologic analysis techniques in 106 pregnant women - 53 heterozygous for hemoglobin (Hb) A and C (AC) and 53 homozygous for the normal Hb A (AA) with similar ages and race ancestry. Eleven (21%) of AC women were alpha-Thal23.7kb heterozygous and 1 (2%) was homozygous, while 12 AA women (23%) were heterozygous. In the AA group, the MCV differed amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
1
9
0
2
Order By: Relevance
“…Borges et al (2001) studied 339 adult outpatients with microcytosis and hypochromia without anemia seen at the University of Campinas Hospital and found 49.9% with α-thalassemia (169 individuals), 145 (42.8%) heterozygotes (-α3.7/αα) and 18 (5.3%) homozygotes (-α3.7/-α3.7). In the Northeast, -α3.7 deletion was investigated by Couto et al (2003) in 106 pregnant women with AC and AA hemoglobin pattern, and 21.7% silent carriers (-α3.7/αα) and 0.9% thalassemic trait (-α3.7/-α3.7) were found. Adorno et al (2005) investigated 590 newborns from Salvador, Bahia, and observed that one hundred and fourteen (22.2%) had α3.7 thalassemia, of whom 101 (19.7%) were heterozygous and 13 (2.5%) homozygous.…”
Section: Introductionmentioning
confidence: 99%
“…Borges et al (2001) studied 339 adult outpatients with microcytosis and hypochromia without anemia seen at the University of Campinas Hospital and found 49.9% with α-thalassemia (169 individuals), 145 (42.8%) heterozygotes (-α3.7/αα) and 18 (5.3%) homozygotes (-α3.7/-α3.7). In the Northeast, -α3.7 deletion was investigated by Couto et al (2003) in 106 pregnant women with AC and AA hemoglobin pattern, and 21.7% silent carriers (-α3.7/αα) and 0.9% thalassemic trait (-α3.7/-α3.7) were found. Adorno et al (2005) investigated 590 newborns from Salvador, Bahia, and observed that one hundred and fourteen (22.2%) had α3.7 thalassemia, of whom 101 (19.7%) were heterozygous and 13 (2.5%) homozygous.…”
Section: Introductionmentioning
confidence: 99%
“…In Southeast Brazil, a frequency of 1.3% of β-thalassemia trait and 0.1% of β-thalassemia major was reported for the general population 12 , while α 2 -thalassemia by a 3.7 kb DNA deletion (α 2 3.7Kb -thalessemia) varied from 20.0% to 25.0% in black populations 13 , and Borges et al 14 found 49.9% of α-thalassemia in adult outpatients seen at the University of Campinas Hospital with microcytosis and hypochromia without anemia. In the Northeast, α 2 3.7Kb -thalessemia was investigated in 106 pregnant women with AC and AA hemoglobin pattern, showing a 21.7% heterozygous and 0.9% homozygous rate for this alteration 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Wambua et al 17 described significantly lower MCV in HbAS than in HbAA regardless of their α status. No differences in MCV were found between HbAC and HbAA, both of them without α-TT, in the study of Couto et al 20. However, Silva et al hypothesised that α-TT does not significantly contribute to the microcytosis in HbAC individuals, and the presence of HbC may itself cause a reduction in the RBC size 21.…”
Section: Discussionmentioning
confidence: 88%
“…Hb A 2 levels, Hb F levels and the percentage of variant Hb were determined by HPLC in the HA-8160 analyser (Menarini Diagnostics, Florence, Italy). According to published studies, subjects with a percentage of variant Hb <35% (for HbS)16 27 or <37% (for HbC)20 21 were considered to have coexistent α-thalassaemia (α-TT). Subjects with a percentage of HbS <35% or percentage of HbC <37% and also ferritin levels <20 ng/mL and/or TSI <20% were considered to have both coexistent iron deficiency and α-TT.…”
Section: Methodsmentioning
confidence: 99%